PLAUR splicing pattern in hereditary angioedema patients' monocytes and macrophages - Ballonová, Lucie; Kulíšková, Petra; Slanina, Peter; Štíchová, Julie; Vlková, Marcela; Hakl, Roman; Litzman, Jiří; Souček, Přemysl; Freiberger, Tomáš (Molecular biology reports, 2023)
BACKGROUND: The PLAUR gene encodes the urokinase-like plasminogen activator receptor (uPAR) and may undergo alternative splicing. Excluding cassette exons 3, 5 and 6 from the transcript results in truncated protein variants whose precise functions have not been elucidated yet. The PLAUR gene is one of several expressed in myeloid cells, where uPAR participates in different cellular processes, including the contact activation system and kallikrein-kinin system, which play an important role in hereditary angioedema (HAE) pathogenesis. A hypothesis about the PLAUR splicing pattern impact on HAE severity was tested. METHODS AND RESULTS: The RT-PCR quantified by capillary electrophoresis was used. Although no significant difference in alternative transcript frequency was observed between healthy volunteers and HAE patients, a significant increase in all cassette exon inclusion variants was revealed during monocyte-to-macrophage differentiation. CONCLUSIONS: PLAUR alternative splicing in monocytes and macrophages neither was different between HAE patients and healthy controls, nor reflected disease severity. However, the results showed an PLAUR splicing pattern was changing during monocyte-to-macrophage differentiation, but the significance of these changes is unknown and awaits future clarification.
Keywords: PLAUR; Leukocytes; Differentiation; Monocytes; alternativní sestřih; leukocyty; Macrophages; HAE; uPAR; monocyty; makrofágy; Angioedemas, Hereditary; Humans; lidé; Monocyte; Alternative Splicing; hereditární angioedémy